Contribución relativa del nanoplancton a la producción primaria y pigmentos fotosintéticos en el Embalse del Río Tercero (Córdoba, Argentina) - Mariazzi, Aldo A.; Romero, María Cristina; Arenas, Patricia (Ecosur, 2024)
A study on primary production and photosynthetic pigments was carried in an eutrophic reservoir (Embalse Río III) during 1980-1981, with the basic purpose of evaluating the importante of nannoplankton (< 30 um) with respect to production and pigments. Nannoplankton had a significative contribution to total primary production and pigments during periods of máximum photosynthetic activity, spring-summer, with 75 and 50% respectively. Nannoplanktonic fraction showed a high photosynthetic effíciency during November 1980 and January 1981 and its activity and numerosity increase was directly related to temperature.